Empirical essays on the long-term outcomes of childhood experiences: Poverty, weather shock and migration - Ermias Gebru Weldesenbet (University of Copenhagen, Department of Economics, 2022)
This PhD thesis contains three self-contained chapters, focusing on the long-term out- come of different childhood experiences. As children are vulnerable to early life experi- ences, whether they have a good or bad start has long-term implications on their life. For that reason, understanding childhood conditions that affect later life outcomes is of paramount importance to policymaking. While there is a large body of literature on developed countries, the empirical investigation of early life conditions for developing countries, especially sub-Saharan Africa, has been constrained mainly due to the lack of longitudinal data following children for a long time. More recently, studies focusing on developing countries are beginning to emerge with the maturity of some longitudinal datasets tracking children, even if it remains much to discover in the context of sub- Saharan Africa. The thesis seeks to address this lacuna in African research by exploring three diverse childhood conditions affecting outcomes in adulthood. [...]
Keywords: 330; Kinder; Eltern; Armut; Intergenerationale Übertragung; Niederschlag; Gesundheit; Internationale Migration; Bildungsabschluss; Nigeria; Tansania